Risk Assessment Applying Logistic Variables at Urban Scale: Case of Gamarra (Peru) - Huivin Vasquez, Jaime; de Brito Junior, Irineu [UNESP]; Chong, Mario (Springer Nature, 2020)
This study evaluates the risks that could result in a disaster in Gamarra (Peru). The baseline focuses on the last mile logistics characteristics such as population density, commercial activities, and infrastructures in square kilometers. Vulnerability of buildings and pedestrian’s speed are also considered. The results show a risk map to help decision makers.
Keywords: Hazard area; Last mile; Logistics; Risk assessment